Light-Controlled Multiconfigurational Conductance Switching in a Single 1D Metal-Organic Wire - Cahlík, Aleš; Ondráček, Martin; Wäckerlin, Christian; Solé, Andres Pinar; Siri, Olivier; Švec, Martin; Jelínek, Pavel (ACS nano, 2024)
Precise control of multiple spin states on the atomic scale presents a promising avenue for designing and realizing magnetic switches. Despite substantial progress in recent decades, the challenge of achieving control over multiconfigurational reversible switches in low-dimensional nanostructures persists. Our work demonstrates multiple, fully reversible plasmon-driven spin-crossover switches in a single π-d metal-organic chain suspended between two electrodes. The plasmonic nanocavity stimulated by external visible light allows for reversible spin crossover between low- and high-spin states of different cobalt centers within the chain. We show that the distinct spin configurations remain stable for minutes under cryogenic conditions and can be nonperturbatively detected by conductance measurements. This multiconfigurational plasmon-driven spin-crossover demonstration extends the available toolset for designing optoelectrical molecular devices based on SCO compounds.
Keywords: one-dimensional system; molecular chains; transport; scanning tunneling microscopy; density functional theory; light-induced switching; spin crossover